Challenges of Practical Space Operations Under the Outer Space Treaty: Operations in a Legal Regime of a Different Era - Horváth, Attila (Shielding Europe with the Common Security and Defence Policy: The EU Legal Framework for the Development of an Innovative European Defence Industry in Times of a Changing Global Security Environment, 2024)
Outer space is of the utmost importance for our society. It is endless, but still limited. It is used to support activities related to business, state, and defence, and while it is replaceable, this replacement would negatively affect our way of life. Its importance also creates a vulnerability that can be exploited by adversaries, however, pure chance can trigger events that can lead to catastrophes. Outer space is, by its very nature, an international environment. Still, the international legal regime regulating it is surprisingly limited compared to its vital importance. This chapter presents several examples wherein the regulations have fallen behind the advance of technology and operations. These shortcomings did not come to light until now only because of practical technology’s inability to realise what is theoretically possible, professionalism of the operators, and sheer luck. It would be unwise to count on these reasons in the future. This chapter organises the examples into the following groups: delimitation of airspace and outer space and operations in the border region; sovereignty and zoning of outer space related to spacecraft; operations of active spacecraft and removal of inactive ones; and defence-related technology development. At the end of each section, questions and suggestions are presented for the legal community to examine and discuss. It is my desire to use this opportunity to support the legislative effort necessary to develop legally binding and enforceable rules and regulations, so as to enable the sustainable long-term use of outer space – a natural resource incomparable to any other.Keywords: spacecraft, Outer Space Treaty, delimitation, sovereignty, dual-use, mesosphere, space debris